High alert medication, medication error in Outpatient Pharmacy Department In Hospital Selayang - Mohamed Noor, Faridah; Raja Zainal Raffik Najmuddin, Raja Diyana (2009)
The main aim of this study was to determine the medication errors at the outpatient pharmacy in Hospital Selayang and the strategies to minimize the prevalence. A retrospective study was conducted that involved collecting the medication errors reports and a convenient sample survey were distributed to the pharmacists working at Hospital Selayang. Generally, the errors occur as a filling error which has the highest percentage of 52.94%. Furthermore, comparison had been done between the general medicine and the high alert medication and the results came out as the general medicine has the higher amount of medication error compared to high alert medication. Most of pharmacists working in Hospital Selayang are aware of the importance of knowledge about High Alert Medication but by having more information about the dispensing system would help them to understand more and learn more , finally can educate patients more precise. In conclusion, it is very clear that the role of pharmacist is very great in preventing and minimizing the medication errors beside the needs of correct prescription writing and other strategies by all of the heath care components.